ASSESSING THE INNOVATION ACTIVITIES OF THE RETAIL COMPANY AFFECTED BY THE COVID-19 PANDEMIC - Aria Ganna Henryanto (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to assess the innovation activities of retail companies affected by the Covid-19 Pandemic. The population and sample in this study are retail trade sub-sector companies listed on the IDX that published an annual report in 2021. Annual attachment coding schemes of retail trade sub-sector companies are based on technical, functional, temporal, spatial and social value components innovations. Data analysis was carried out with NVIVO. The analysis results show that the three main innovations carried out by retail companies during the Covid-19 Pandemic are delivery innovations, social initiatives, and educational innovations. In addition, another finding is that the company with the highest level of innovation is MCASH.